MEMBENTUK GENERASI BERWAWASAN GLOBAL DAN BERKARAKTER LOKAL: KAJIAN LITERATUR TENTANG PERSPEKTIF GLOBAL DALAM KURIKULUM SEKOLAH DASAR - Ilfan Hakim; Nurzaitun Rahmadani; Reva Ramadhani; Tania rahayu putri; Sherly auliani; Heri Effendi; Hendrizal (STKIP Subang, 2026)
The increasing demand for global competence in the twenty-first century has encouraged elementary education to integrate global perspectives into the curriculum while maintaining local cultural values. However, the implementation of global-oriented learning often faces challenges in balancing international awareness with the preservation of students’ local identity and character. This study aims to examine the integration of global perspectives in the elementary school curriculum and to explore strategies for developing students who possess global insight while sustaining strong local character. The research employed a qualitative literature review method by systematically analyzing relevant books, peer-reviewed journal articles, policy documents, and previous studies concerning global education, elementary curriculum, and character education. The collected literature was critically reviewed, synthesized, and interpreted to identify key concepts, implementation approaches, and educational implications. The findings indicate that integrating global perspectives into the elementary curriculum can effectively enhance students’ critical thinking, intercultural communication, collaboration, and global citizenship competencies when accompanied by the reinforcement of local wisdom, cultural identity, and national values. Furthermore, the literature emphasizes that contextual learning, project-based activities, culturally responsive pedagogy, and teacher readiness are essential factors in achieving a balanced curriculum that promotes both global competence and local character development. Therefore, the successful integration of global perspectives requires curriculum innovation, professional teacher development, and continuous collaboration among schools, families, and communities to prepare students for global challenges without diminishing their cultural roots.